Interpersonal sensitivity on college freshmen’s depression: A moderated moderation model of psychological capital and family support - Xu, Haibo; Peng, Lixin; Wang, Zhen; Zeng, Ping; Liu, Xin (Frontiers in Psychiatry, 2022)
Background: The prevalence of depressive symptoms become more higher among college freshmen, and interpersonal sensitivity is an important predictor. Combining internal and external positive resources can effectively prevent and alleviate depression. The aim of this study is to explore the moderating role of psychological capital (PsyCap) in the relationship between interpersonal sensitivity and depression, and the moderating effect of family support on the conditional influence of PsyCap among Chinese college freshmen. Methods: A cross-sectional mental health survey was performed and the anonymous self-reported questionnaire including Patient Health Questionnaire, interpersonal sensitivity subscale of Symptom Checklist-90, Psychological Capital Questionnaire 24 and Perceived Social Support from Family was distributed to the freshmen. Pearson coefficient was employed to describe correlations between variables. The PROCESS macro and slope difference test were used to explore the moderating role of PsyCap and family support in the relationship between interpersonal sensitivity and depression. Results: the prevalence of depression among freshmen was 30.89% (694/2247). Correlation analysis revealed that depression was negatively related with PsyCap (r = -0.187, p < 0.001) and family support (r = -0.193, p < 0.001), and positively related with interpersonal sensitivity (r = 0.399, p < 0.001). The moderation analysis showed that PsyCap negatively moderated the positive relationship between interpersonal sensitivity and depression (β = -0.159, p < 0.001). The study further displayed that family support played a moderating role in the conditional influence of PsyCap (β = 0.076, p < 0.01). The slope difference test further showed that family support weakened the effect of interpersonal sensitivity on depression of freshmen when they are with low PsyCap. Conclusions: More attention should be paid to freshmen’ mental health and interpersonal interaction problems. For freshmen with interpersonal sensitivity and depression, mental health departments can conduct PsyCap development interventions to alleviate psychological symptoms. Freshmen themselves should also seek family support in time, but those individuals with high PsyCap should seek appropriate family support to maintain their autonomy.